PENGARUH PERBEDAAN JENIS IKAN TERHADAP KARAKTERISTIK GEL SURIMI - Olvie Tiana Sarie; Andi Noor Asikin; Indrati Kusumaningrum (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Surimi is a minced fish that washed with water and added cryoprotectants, can be made using various types of fish, especially for white fleshed fish. This study aimed to determine the best characteristics of surimi from various types of fish. The treatments were P1 (Belida; Chitala sp), P2 (Nila; Oreochromis niloticus), P3 (Biji Nangka; Openeus moluccensis) and P4 (Bandeng; Chanos-chanos). The parameters tested in this study were yield, moisture content, protein content, pH, and folding test. This study applied Completely Randomized Design (CRD) with four treatments and three replications. The results of this study showed that the type of species was significant affected the yield parameters, protein content and pH, but were not significant to the moisture content. The high protein content was found in P3 (Upeneus moluccensis) of 21.1%. The best folding test for surimi gel was found in P4 (milkfish) with a value of 4, included in grade A.